Social configurations in the moment of post-foundationalism - Jong, Abbas (Frontiers in Sociology, 2023)
Modern social sciences arose during a period of classical modernity in which discovering universal rules between distinct phenomena was the most prominent criterion of scientific knowledge. Social phenomena were considered in the form of isolated, determined, standardized, and regulated objects whose knowledge, like that of the natural sciences, depended on the understanding of universal laws. The accidental and the contingent were eliminated in favor of universal laws. With the intensifying of modernity and the transition to late and liquid modernity, and by suspending many dominant cognitive categories, this kind of essentialist foundationalism was attacked by a variety of anti/non-foundationalist criticism that subscribed to either plural grounds or groundlessness, a bottomless ground in which scientific knowledge at a high level lost its significance. This predicament has given rise to several biases and antinomies in modern social theory. By addressing some of these predicaments and antinomies, including foundationalism/non(anti-)foundationalism, agency/structure, the individual/society, essentialism/relativism, and universalism/singularism, the present article strives to propose the idea of social configurations as a solution to overcome them, and through this endeavor, it is indicated that considering these configurations can effectively explain emerging and interrelated global phenomena. By prioritizing the conditions of possibility for social phenomena, and taking into account their contingency, as well as the incompleteness and partiality of their foundations, social configurations are considered as units at the level of the particular whose relationality, indeterminacy, interdependence, and fluidity constitute their central features.